Optimizing Cayenne Pepper Growth through Liquid Organic Fertilizer and NPK Fertilizer Application - Yohanes Parlindungan Situmeang; Made Suarta; Dionisius Rofanno Syahputra Assan (Agriwar Journal, 2023)
This research aims to determine the effect of applying liquid organic fertilizer and NPK fertilizer and their interactions, on the growth and yield of cayenne pepper plants (Capsicum frutescens L.) which was carried out in Kupang City, Oebobo District, East Nusa Tenggara starting in June 2023 until September 2023. This research method uses a randomized block design (RBD) arranged factorially with 2 factors. The first factor tried was liquid organic fertilizer (P) which consisted of 4 concentration levels, namely: P0 (0 cc L-1 water), P1 (25 cc L-1 water), P2 (50 cc L-1 water), and P3 (75 cc L-1 water). Meanwhile, the second factor that was tried was NPK (N) fertilizer which consisted of 4 dose levels, namely: N0 (0 kg ha-1), N1 (150 kg ha-1), N2 (300 kg ha-1) and N3 (450 kg ha-1). There were 16 combination treatments, each repeated 3 times so that 48 cayenne pepper plants were needed. This research results showed that the interaction between liquid organic fertilizer and NPK fertilizer had a real influence on almost all the variables observed except stem diameter and number of flowers formed. The highest average fruit weight per plant was obtained at a liquid organic fertilizer concentration of 25 cc L-1 water (P1), namely 110.17 g, or an increase of 12.32% when compared to treatment without liquid organic fertilizer, namely 98.08 g. Meanwhile, with NPK fertilizer treatment, the highest average fruit weight per plant was obtained at a dose of 150 kg ha-1, namely 115.25 g, or an increase of 26.41% when compared to the control (N0), which was only 91.17 g. The interaction of the POC concentration treatment of 75 cc L-1 water with an NPK fertilizer dose of 150 kg ha-1 (P3N1) gave the highest fruit weight gain of 133.00 g (P3N1) although supporting variables such as the growth of cayenne pepper plants gave different results. different in the treatment of liquid organic fertilizer concentration and NPK fertilizer dosage.